SOUTH AFRICA AND THE SADC STAND-BY FORCE - Mandrup, Thomas (Scientia Militaria - South African Journal of Military Studies, 2011)
The regional powerhouse, South Africa, has since the introduction of the nonracial democratic dispensation in 1994, played a central and important role in theformation of both the regional and continental security architecture. With theestablishment of the Southern African Development Community (SADC) in 1992,one of the central areas of collaboration for the community was envisioned to besecurity, understood within a broadened human security framework. Security wastherefore from the outset one of the cornerstones of integration in the SADC. It wasbelieved that the formation of a security community would help dismantle theenmities that had plagued regional relations during the apartheid era. For someparties, institutionalisation of relations pointed to a means of stabilising anddisseminating a particular order. Such institutions depict the power relationsprevailing at the time of their establishment, which, however, can change over time(Cox 1981:136). The integration ambition surrounding security correlated with theambitions of South Africa, the new democratic government in the regionalpowerhouse. South Africa and its overall foreign policy ambitions desired thepursuit of peace, democracy and stability for economic growth and development inthe region and within South Africa itself.